2021
DOI: 10.1021/acs.est.1c01103
|View full text |Cite
|
Sign up to set email alerts
|

Plastic Products Leach Chemicals That Induce In Vitro Toxicity under Realistic Use Conditions

Abstract: Plastic products contain complex mixtures of extractable chemicals that can be toxic. However, humans and wildlife will only be exposed to plastic chemicals that are released under realistic conditions. Thus, we investigated the toxicological and chemical profiles leaching into water from 24 everyday plastic products covering eight polymer types. We performed migration experiments over 10 days at 40 °C and analyzed the migrates using four in vitro bioassays and nontarget high-resolution mass spectrometry (UPLC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
100
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 133 publications
(108 citation statements)
references
References 40 publications
(83 reference statements)
7
100
1
Order By: Relevance
“…Validated methods to interpret the huge amounts of information generated from these analyses are, in our experience, critical. Moreover, targeted and nontargeted screenings can identify substances associated with plastics, but they must be combined with toxicological data (Zimmermann et al 2020(Zimmermann et al , 2021. We recommend that bioanalytical tools, health data (ideally from prospective longitudinal cohort studies), cheminformatics, and holistic human health risk analyses should be integrated to obtain meaningful information about potential relationships between chemical signals and their toxicity for child health.…”
Section: Analytical Tools To Characterize Nmpsmentioning
confidence: 99%
See 2 more Smart Citations
“…Validated methods to interpret the huge amounts of information generated from these analyses are, in our experience, critical. Moreover, targeted and nontargeted screenings can identify substances associated with plastics, but they must be combined with toxicological data (Zimmermann et al 2020(Zimmermann et al , 2021. We recommend that bioanalytical tools, health data (ideally from prospective longitudinal cohort studies), cheminformatics, and holistic human health risk analyses should be integrated to obtain meaningful information about potential relationships between chemical signals and their toxicity for child health.…”
Section: Analytical Tools To Characterize Nmpsmentioning
confidence: 99%
“…Plastic products have also been found to contain a cocktail of more than 40,000 chemicals ( Zimmermann et al. 2020 ), and certain plastics have been shown to leach over 80% of their chemicals into water, highlighting the potential for human exposure ( Zimmermann et al. 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 161 These results indicate that particles may induce physical effects beyond chemical toxicity, even though at an order of magnitude highly exceeding environmental relevant concentrations. In an in vitro assessment from the same authors, 148 leachates from PLA showed a strong baseline toxicity, similar to leachates from PVC and polyurethane (PU), but once more at concentrations exceeding expected ones in the environment. These early assessments on the toxicity of leachates from biobased plastics indicate that even though individual additives may not be considered toxic for aquatic organisms (see Section 4, Table 1 ), complex mixtures of additives released in the environment may induce toxicity, which may be enhanced by weathering processes of the materials.…”
Section: Ecotoxicology Of Microplastics and Leachates From Biobased M...mentioning
confidence: 93%
“…Due to the continued availability of plastic in the open environment, weathering causes fragmentation of plastic material into microplastic, which exacerbates the problem (Verla et al ., 2019) and have become a hotspot for antibiotic-resistant microorganisms to form biofilms (Kirstein et al ., 2018; Dussud et al ., 2018; Jacquin et al ., 2019), revealing a wide range of antibiotic resistance genes of pathogenic bacteria growing on microplastics (Jacquin et al ., 2019). There are reports of contamination in every level of the food chain, including human beings (Cox et al ., 2019; Monteiro et al ., 2018; Wright & Kelly, 2017; Zhou et al ., 2020; Zimmermann et al ., 2021).…”
Section: Introductionmentioning
confidence: 99%